PENERAPAN TIME-DRIVEN ACTIVITY BASED COSTING PADA PERHITUNGAN HARGA POKOK PRODUK JASA DI PT ERNEST ADVISORY - Kristina, Indira; Faliany, L Jade (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2016)
This research aimed to calculate the cost of the product PT Ernest Advisory services using Time-Driven Activity Based Costing (TDABC). TDABC is a method of calculating the cost-based activity that is controlled by time so the cost of goods produced to be more accurate. The method used in this research is a case study in PT Ernest Advisory using data from 2015. Based on these data, the authors calculated the cost of using TDABC. Calculations using TDABC generate product cost services Tax Audit and Tax Objection Rp 14,260,620, Monthly Tax Compliance Rp 5.03328 million, Tax Appeal Rp 18.981 million, Tax Review Rp 12,920,700 and Rp Transfer Pricing Documentation 13.5201 million.